An English translation of Bachofen's Mutterrecht (Mother right) (1861) a study of the religious and juridical aspects of gynecocracy in the ancient world - Bachofen, Johann Jakob, 1815-1887.; Partenheimer, David, 1949- (Lewiston : Edwin Mellen Press, 2007)
Mutterrecht (Mother Right) by Johann Jakob Bachofen was the seminal document of the 19th century concerning the role of women in ancient societies. Bachofen documented that motherhood is the source of human society, religion, morality, and decency in societies including Lycia, Crete, Greece, Egypt, India, Central Asia, Northern Africa, and Spain. He concluded the work by connecting ancient mother right with Christianity. Bachofen's theory of cultural evolution incited a virtual 'mother-mania' among ethnologists, social philosophers, and even writers, among them Lewis Henry Morgan, Friedrich En.
Title Page; Copyright Page; Table of Contents; Translator's Introduction; Preface and Introduction; Lycia; Crete; Athens; Lemnos; Egypt; India and Central Asia; Orchomenus and the Minyans; Elis; Epizephyrian Locrians; Lesbos; Mantinea; Pythagoreanism and Subsequent Doctrines; Cantabri; Lithographs; Works Cited; References; Index.
Print version record.
Keywords: Matriarchy -- History -- To 1500.; Social Science; FAMILY & RELATIONSHIPS -- Alternative Family; FAMILY & RELATIONSHIPS -- Reference; Matriarchy; To 1500; Electronic books; History; Electronic books